1985
DOI: 10.1037/0021-9010.70.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Task-based performance appraisal for blue-collar jobs: Evaluation of race and sex effects.

Abstract: Court standards for job analysis were used to develop a task-based performance appraisal instrument for use with multiple blue-collar jobs in a small, foamed plastics plant. The instrument consisted of 10 performance categories that were rated in terms of importance to the job and performance. Race and sex effects in performance appraisal scores and overall performance ranking of 150 employees in three jobs were analyzed with separate factorial analyses of covariance. Neither race nor sex effects were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…For example, no sex (or race) effects were reported in field settings where job analysis was used to develop a task-based performance appraisal instrument (Thompson & Thompson, 1985), and no gender differences were reported when rating familiar tasks in work situations where feedback was available (Shore & Thornton, 1986). Conversely, students tended to give women professors higher ratings (Dobbins, Cardy & Truxillo, 1988), and raters holding traditional stereotypes of women tended to be less accurate when ratings were made for administrative (versus developmental) purposes.…”
Section: Raterlratee Personal Characteristicsmentioning
confidence: 99%
“…For example, no sex (or race) effects were reported in field settings where job analysis was used to develop a task-based performance appraisal instrument (Thompson & Thompson, 1985), and no gender differences were reported when rating familiar tasks in work situations where feedback was available (Shore & Thornton, 1986). Conversely, students tended to give women professors higher ratings (Dobbins, Cardy & Truxillo, 1988), and raters holding traditional stereotypes of women tended to be less accurate when ratings were made for administrative (versus developmental) purposes.…”
Section: Raterlratee Personal Characteristicsmentioning
confidence: 99%
“…For example, Rosen and Jerdee (1973) found that male managers discriminated against female employees when making personnel decisions regarding promotion, professional development, and supervision. Perhaps enforcement of Title VII has had some effect because, 12 years later, Thompson and Thompson (1985) found that the gender of an appraisee had no effect on performance appraisal ratings in certain settings.…”
Section: Relevant Researchmentioning
confidence: 99%
“…Dozens of conceptualizations of what can and should be measured within an individual performance system have been put forth in the literature and in practice (five-, four-, three-, two-point rating scales; competency based, production based, objective based, task based, behavior based, etc. ; e.g., Benson, Buckley, & Hall, 1988;Bommer, Johnson, Rich, Podsakoff, & MacKenzie, 1995;Borman, 1979;Catano, Darr, & Campbell, 2007;Fay & Latham, 1982;Goffin, Jelley, Powell, & Johnston, 2009;Jelley & Goffin, 2001;Johnson, 2001;Latham, Fay, & Saari, 1979;Thompson & Thompson, 1985;Tziner & Kopelman, 2002). Irrespective of the manner in which evaluations happen, judgments are made and decisions about rewards and roles in the future are based on those judgments.…”
Section: Performance Is Always Evaluatedmentioning
confidence: 99%